An Investigatory Project of Corn (Zea mays) Grain Starch as Alternative Bioplastic: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
One of the biggest problems in our environment is waste pollution. Low-density polyethylene(LDPE) plastics are non-biodegradable, and improper disposal of used plastics causes solidwaste to accumulate and harm the environment. To address the issue above, the researcherscame up with the idea of generating bioplastic using starch as a construction material, whichcould be a solution to decrease waste pollution.The results of the study are acceptable for both chemical and environmental engineers interms of construction materials, design and procedure, environmental impact, durability, andpresentation. The results are also acceptable for both chemical and environmental engineersin terms of environmental impact, durability, and presentation.It indicates that there is no significant difference between and among the assessments of thetwo groups of respondents in terms of construction materials, design and procedure,environmental impacts, durability, and presentation. The overall mean of the chemicalengineers is 3.34 with a variance of 0.034, a t-computed of 1.282, a degree of freedom of 8,and a t-critical of 3.355. The t-computed is t-critical; therefore, the assessment of the chemicalengineers is highly acceptable. The overall mean of environmental engineers is 3.19 with avariance of 0.034, a t-computed of 1.282, a degree of freedom of 8, and a t-critical of 3.355.The t-computed is t-critical; therefore, the assessment of environmental engineers isacceptable. There is no significant difference between the assessments of the two groups ofrespondents in terms of the aforementioned variables. For further enhancement andimprovement of the project, the ensuing discussions and the recommendations proposed areas follows: perform a method for bioplastic testing to know the properties of the bioplastic. Fora better outcome, try to generate the product inside the testing center.
Keywords: Chemical Engineering